Sistem Pembangkit Listrik Panel Surya Atap Model 0n-Grid Dengan Kapasitas 62.4 kWp - Suyanto, Muhammad; Eko Pambudi, Prasetyono; Wildan Chotami, Faisal (Jurnal Teknologi, 2023)
Solar panels are one of the renewable alternative energies that can be used as primary energy in generating electrical energy through the Solar Power Plant (PLTS) system. The main ingredient of PLTS is the radiation produced by the sun every day.On the roof of the Smart and Green Learning Center (SGLC) Building, Faculty of Engineering UGM, an on-grid solar power plant with a capacity of 62.4 kWp is installed with a total of 156 solar panel modules. The power generated by PLTS can reach 205.627 kW or 183 kWh in sunny conditions in cloudy the power generated by PLTS is 73.781 kW or 66 kWh with the amount of light intensity absorbed reach 110,966 Lux and the lowest value to be reaching 3,407 Lux. The amount of solar irradiation received is directly proportional to the amount of solar light intensity produced with the largest radiation reaching 877 W/m2 while the lowest radiation is 27 W/m2. The aims to know the value of the power generated by PLTS through the inverter and to determine the value of economic savings from the installed PLTS